QISHASH DIYAT DALAM HUKUM PIDANA ISLAM LEBIH MENCERMINKAN KEADILAN DARI SISI KORBAN - Mahendra Kusuma; Rosida Diani (JURNAL DINAMIKA, 2022)
Qishash is a death penalty in Islamic criminal law. However, it is not universally applicable. In other words, the perpetrator can avoid qishash if the victim's heirs forgive him by paying a diyat. As demonstrated in several Islamic countries, the qishashdiyat punishment has numerous advantages. Among the difficulties that will be encountered in enforcing these punishments in our country are the following: qishash punishment is considered cruel and inhumane, and will lead to allegations of the Islamization of minority groups. This is what makes Islamic parties not one opinion. Qishash merupakan hukuman mati dalam hukum pidana Islam. Namun penerapannya tidak secara mutlak. Artiny, pelaku dapat terhindar dari qishash apabila dimaafkan oleh ahli waris korban dengan membayar diyat. Hukuman qishash diyat mempunyai banyak kelebihan, dan ini telah terbukti di beberapa negara Islam. Hambatan yang akan dihadapi dalam memberlakukan hukuman tersebut di negara kita, antara lain: hukuman qishash dianggap kejam dan tidak manusiawi, akan menimbukan dugaan adanya Islamisasi dari kelompok minoritas. Inilah yang membuat partai-partai Islan tidak satu pendapat.